Impact of Biofuel Adoption on Health, Environment, and Energy in Rural and Urban Applications - Ravikant Nanwatkar; Gaikwad Pankaj; Giri Shriyash; Hyalij Sarthak; Jadhav Sarthak (International Journal of Environmental Noise and Pollution Control, 2025)
The adoption of biofuels as an alternative to conventional fossil fuels has garnered significant attention due to its potential to address pressing global challenges related to health, environmental sustainability, and energy security. This research investigates the multifaceted impact of biofuel adoption in rural and urban settings, focusing on health benefits, environmental implications, and energy sustainability. Biofuels, derived from renewable biomass sources, offer a cleaner combustion profile, reducing harmful emissions such as particulate matter, CO, and NOx, which are major contributors to respiratory and cardiovascular diseases. In rural areas, biofuels present a viable substitute for traditional cooking fuels like firewood and LPG, mitigating indoor air pollution and associated health risks while reducing deforestation and greenhouse gas emissions. In urban contexts, biofuels contribute to reducing vehicular emissions and enhancing air quality. Furthermore, the transition to biofuels promotes energy diversification and independence, particularly in energy-insecure regions, and supports the circular economy by utilizing agricultural and organic waste. This study identifies key barriers, including technological, economic, and policy challenges, that hinder widespread biofuel adoption. It also underlines how education and outreach to the community may promote acceptability and successful operation. The findings underscore the potential of biofuels to serve as a bridge toward a sustainable energy future while simultaneously addressing critical health and environmental concerns in both rural and urban landscapes.
Keywords: Biofuels; Environmental sustainability; Health; energy security; fossil fuels; policy challenges